2011
DOI: 10.1002/pd.2831
|View full text |Cite
|
Sign up to set email alerts
|

Fetal cardiac evaluation at 11–14 weeks by experienced obstetricians in a low‐risk population

Abstract: First-trimester assessment of the fetal heart is feasible in a low-risk population when performed by experienced obstetricians. However, although most types of CHD can be diagnosed early in pregnancy, some may become apparent later in gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 28 publications
1
77
0
4
Order By: Relevance
“…15 Similarly, Perisco et al 16 showed a 93.1% detection rate for congenital heart defects in a group of 886 patients including 100 cardiac anomalies. Also, Volpe et al 17 demonstrated that the direct assessment of the heart at 11 to 14 weeks is a feasible method of screening for congenital heart defects in an unselected population. Direct assessment of the fetal heart in the first trimester to search for congenital heart defects in a high-risk population revealed that the examiner's experience and the selection of patients are among the most important factors that have an impact on detection of congenital heart defects.…”
Section: Discussionmentioning
confidence: 99%
“…15 Similarly, Perisco et al 16 showed a 93.1% detection rate for congenital heart defects in a group of 886 patients including 100 cardiac anomalies. Also, Volpe et al 17 demonstrated that the direct assessment of the heart at 11 to 14 weeks is a feasible method of screening for congenital heart defects in an unselected population. Direct assessment of the fetal heart in the first trimester to search for congenital heart defects in a high-risk population revealed that the examiner's experience and the selection of patients are among the most important factors that have an impact on detection of congenital heart defects.…”
Section: Discussionmentioning
confidence: 99%
“…Tables 1 and 2 summarizes some of the largest and most significant studies on the detection of CHD using early fetal echocardiography in high-risk and low-risk pregnancies. 14,[17][18][19][20][21][22][24][25][26][34][35][36][37][38][39][40][41][42][43][44][45][46] Obviously, studies in unselected population report less encouraging results, with lower visualization rates and detection rates. The largest series was published by Bronshtein et al 20 They report the diagnosis of 173 cases of CHD over 36,323 fetuses evaluated by transvaginal ultrasound at 11 to 17 weeks' gestation over a 14-year period of time, with 99% of scans performed at 14 to 16 weeks' gestation and 86% of them in low-risk population.…”
Section: Diagnosis Of Chdmentioning
confidence: 99%
“…Die Arbeitsgruppe aus Bari veröffentlichte zwei Arbeiten, in denen sie an einem High-riskKollektiv [29] und an einem Lowrisk-Kollektiv [47] …”
Section: Transiente Hinweiszeichenunclassified